Removal of Toxic Chromium(VI) by the Adsorption of Activated Carbons Prepared from Mahua Shells - Ramesh Babu, C.; Raghun, P.; Jayaveera, K.N. (Asian Journal of Chemistry, 2016)
Removal of toxic Cr(VI) in aqueous medium was investigated using activated carbon adsorbents prepared from Mahua seed shells. The pH effect, concentration, adsorbent dosage and contact time period were studied in batch experiment. The removal of Cr(VI) was in general most effective at pH range 2.0-4.0. Activated carbons are prepared at 800 ± 50°C temperature. One is non-impregnated and the remaining three are impregnated with zinc chloride in 1:1, 1:2, 1:3 ratio. Important characteristics of activated carbons are also investigated. The data for all the adsorbents fit well to the Freundlich adsorption isotherm. The removal of Cr(VI) is around 97% was observed with 1: 2 impregnated activated carbon at pH 3.0 whereas other adsorbents showed much lower activities.